BENZENE PRODUCTION FROM NATURAL GAS IN ARUN GAS FIELD: PROCESS DESIGN AND ECONOMIC EVALUATION - Meyland, Meyland; Aletheia, Samuel Pangeran; Kurniawan, Yosia Gabriel; Tanuwidjaja, Kornelius Sophiano; Michelle, Michelle (CHEMTAG Journal of Chemical Engineering, 2024)
This study designs a benzene production plant from natural gas in the Arun Gas Field, Aceh, Indonesia, with a focus on sustainability and economics. The plant could support Indonesia's government efforts in achieving the Enhanced Nationally Determined Contribution and carbon credit objectives. Using DWSim simulation, the processes modeled consists of natural gas purification, dehydroaromatization reaction, and benzene separation. The results demonstrate high efficiency in producing benzene with a purity of 99.5%-wt. Economic analysis indicates that the investment in this plant is financially viable, with an internal rate of return of 12.2%, a payback period of 7.6 years, and an 8.93% return on investment.  By combining sustainability and economic profitability, this research provides a foundation for the implementation of an environmentally friendly and sustainable benzene production plant in the Arun Gas Field.